Kajian Etnobotani dalam Makanan Tradisional Wa’ai Zamu sebagai Bentuk Warisan Budaya Masyarakat Ende - Wae, Veronika P. Sinta Mbia; Nona, Hadijah; Permatasari, Intan; Gaga, Florentinus; Sado, Thomas Wayan Pao (Biocaster : Jurnal Kajian Biologi, 2025)
This research is an ethnobotanical study of the traditional food Wa'ai Zamu, a form of cultural heritage of the Ende people, East Nusa Tenggara. The objective was to document local knowledge regarding the use of plants in making Wa'ai Zamu and the cultural values it embodies. The study employed a qualitative approach with ethnographic methods. Data were obtained through in-depth interviews with 10 key informants selected purposively, consisting of traditional leaders, women traditional food processors, and local cultural experts. Triangulation techniques were used through participant observation and literature review to strengthen the validity of the data. The results indicate that Wa'ai Zamu uses various types of local plants with nutritional value and symbolic functions in traditional rituals. Information regarding nutritional content comes from informants and is partially supported by previous literature references. This study demonstrates that traditional foods serve not only as daily consumption but also represent the identity and cultural continuity of the Ende people. Documenting this knowledge is crucial for preserving intangible cultural heritage, which is vulnerable to modernization.